What contemporary viruses tell us about evolution: a personal view - Moelling, Karin (Springer Vienna, 2013)
Recent advances in information about viruses have revealed novel and surprising properties such as viral sequences in the genomes of various organisms, unexpected amounts of viruses and phages in the biosphere, and the existence of giant viruses mimicking bacteria. Viruses helped in building genomes and are driving evolution. Viruses and bacteria belong to the human body and our environment as a well-balanced ecosystem. Only in unbalanced situations do viruses cause infectious diseases or cancer. In this article, I speculate about the role of viruses during evolution based on knowledge of contemporary viruses. Are viruses our oldest ancestors?